Building Teacher Capacity in Designing Digital Authentic Assessments Oriented toward Education for Sustainable Development - Emiliannur emiliannur (Fakultas MIPA Universitas Negeri Padang, 2026)
Education for Sustainable Development (ESD) aims to develop competencies that empower individuals to reflect on their own actions while considering their social, cultural, economic, and environmental impacts, both present and future, from local and global perspectives. The integration of ESD concepts into assessment instruments has become an urgent necessity to foster learners’ critical awareness of sustainability issues. Authentic assessment is often positioned as a magical solution in education, implemented to address various complex problems. This activity aims to Building Teacher Capacity in Designing Digital Authentic Assessments Oriented toward Education for Sustainable Development (ESD). This community service activity in the form of mentoring uses a method that consists of several stages. The first stage is the preparation stage, the second stage is the guided and independent activity stage, and the third stage is monitoring. This activity received a positive response from the participants, namely the teachers of MAN 2 Bukittinggi, with more than half of the participants stating that the training was interesting, beneficial, and effective.